Literature review on the genetic variability of Escherichia coli in clinical isolates: relationship with antibiotic resistance and virulence factors - Rum, Magfirah Rahimah; Muthiadin, Cut (Tropical Genetics, 2025)
Escherichia coli is a natural flora found in the intestine, but Escherichia coli is also a major repository of resistance genes that may be responsible for treatment failure in humans and animals. This study aims to understand and evaluate the genetic variability of Escherichia coli in clinical isolates and to determine the correlation between genetic variability and antibiotic resistance. This study uses a literature review method. This study presents the results of a search for studies related to the topic, namely the genetic variability of Escherichia coli in clinical isolates and the relationship with antibiotic resistance and virulence factors. The criteria for articles used as data are articles published in the last 10 years, namely from 2015 to 2025. Based on the research that has been done, it can be concluded that genetic variability in Escherichia coli in clinical isolates plays an important role in adaptation, pathogenicity, and antibiotic resistance. Mechanisms such as horizontal gene transfer (HGT), mutations, and genome rearrangements allow E. coli to acquire virulence genes and antibiotic resistance genes, such as genes encoding extended-spectrum β-lactamases (ESBLs) including TEM, SHV, and CTX-M. These genes are often located on mobile plasmids, which support the spread of resistance between bacterial strains and species, complicating infection control and clinical treatment.